Innovative Applications of Intelligent Technology in Infant Care Products: A Study on the Design of Bottle Warmers and Milk Warmers - Yifang Xie (Innovation in Science and Technology, 2024)
This paper delves into the innovative application of intelligent technology in the design of infant care products, with a particular focus on the design of smart bottle warmers and milk warmers, and their impact on user experience. The study begins by analyzing the current market demands and limitations of existing products in the field of infant care products, followed by a detailed discussion of the design features, technological advantages, and user experience of HAUTURE brand products. Through an in-depth analysis of the temperature control technology of the smart bottle warmer, the user interface design, and the dual-sealing system and vibration reduction and noise reduction technology of the milk warmer, this paper reveals how intelligent technology enhances product performance and user satisfaction. In addition, this paper examines the role of user feedback in product design improvement and proposes solutions to technical challenges. Finally, it provides an outlook on the future development trends of intelligent infant care products, predicting how intelligent technology will further shape innovation in this field.